The role of phylogenetic scale in Darwin's naturalization conundrum in the critically imperilled pine rockland ecosystem. Issue 4 (3rd February 2021) - Trotta, Lauren B.; Siders, Zachary A.; Sessa, Emily B.; Baiser, Benjamin
Abstract: Aim: We expand on community phylogenetic approaches to Darwin's Naturalization Conundrum by considering phylogenetic scale, comprised of phylogenetic grain and extent. We assess relatedness between invasive, non‐native and native plant species at multiple depths in the phylogeny (i.e. phylogenetic grain) and across multiple clades (i.e. phylogenetic extents) at regional and local spatial scales in the highly fragmented, critically imperilled pine rockland ecosystem. Location: Miami‐Dade County, Florida, USA. Methods: We used two metrics differing in phylogenetic grain to determine whether invasive or non‐native species were more closely related to native species in the regional pool and at 33 habitat fragments. At both spatial scales, we altered phylogenetic extent from all vascular plants to four smaller phylogenetic domains (Monilophyte, Gymnosperm, Monocotyledon and Dicotyledon) and assessed whether the interpretation of relatedness changed. Results: For the regional pool and at a broad phylogenetic grain, non‐native species were more closely related to the native community than invasive species were for all phylogenetic extents (i.e. support for Darwin's Naturalization Hypothesis, DNH), and at a fine phylogenetic grain for only two phylogenetic extents. At the local scale, there was limited support for DNH across all phylogenetic extents. In Monocotyledons, support for DNH was more prevalent at the fine phylogenetic grain, while Dicotyledons showed support for DNH at the broad phylogenetic grain. Main conclusions: In the pine rockland flora, we found either support for DNH or no difference in relatedness between non‐native ‐to‐ native and invasive‐ to‐ native species. However, patterns of relatedness varied across spatial and phylogenetic grain and, critically, this variability is highly dependent on the phylogenetic extent considered. By explicitly assessing the interactions between spatial scale and phylogenetic scale, we show that support for DNH was context dependent, and findings at smaller phylogenetic extents rarely agreed with findings at the larger phylogenic extent.